2012
DOI: 10.5114/ceji.2012.32730
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA (miRNA) and the immune system

Abstract: During the last few years, several types of small regulatory RNA-sRNA have been described, which participate in gene silencing. So far, the largest group of sRNA described is microRNA, which are multifunctional molecules that participate in many physiological and pathological processes in mammals. As it turns out, the molecules are also related to the immune system, and their participation was described in both innate and adaptive immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Evidence has demonstrated that miRNAs suppress expression of relevant target genes in hematopoietic cells, and subsequently change the differentiation of hematopoietic progenitor cells. miRNAs may also be involved in the functional regulation of hematopoietic stem cells and immune cells (20). MDSCs are immunoregulatory cells originated from hematopoietic stem cells, which may also be regulated by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has demonstrated that miRNAs suppress expression of relevant target genes in hematopoietic cells, and subsequently change the differentiation of hematopoietic progenitor cells. miRNAs may also be involved in the functional regulation of hematopoietic stem cells and immune cells (20). MDSCs are immunoregulatory cells originated from hematopoietic stem cells, which may also be regulated by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In cases when such regulation is impaired, autoimmunity develops [32]. In the last twenty years, substantial progress towards understanding the immune mechanism has been made, and it is clear that miRNAs play an important part in this immune regulation [33].…”
Section: The Role Of Mirna In Immune Responsementioning
confidence: 99%
“…The proper functioning of individual human organ systems, conditioned by efficient communication between systems and elements of each of these systems, forms the fundamentals of homeostasis. Communication takes place through endo‐, para‐, and autocrine pathways via protein messengers, hormones, neurotransmitters, cytokines, and short RNA molecules (Sikora, Ptak & Bryniarski, 2011; Hukowska‐Szematowicz, Tokarz‐Deptuła & Deptuła, 2012).…”
Section: Introductionmentioning
confidence: 99%